LazyPIM: An Efficient Cache Coherence Mechanism for Processing-in-Memory - Boroumand, Amirali; Ghose, Saugata; Patel, Minesh; Hassan, Hasan; Lucia, Brandon; Hsieh, Kevin; Malladi, Krishna T.; Zheng, Hongzhong; Mutlu, Onur (IEEE Computer Architecture Letters (CAL), 2016)
Processing-in-memory (PIM) architectures cannot use traditional approaches to cache coherence due to the high off-chip traffic consumed by coherence messages. We propose LazyPIM, a new hardware cache coherence mechanism designed specifically for PIM. LazyPIM uses a combination of speculative cache coherence and compressed coherence signatures to greatly reduce the overhead of keeping PIM coherent with the processor. We find that LazyPIM improves average performance across a range of PIM applications by 49.1% over the best prior approach, coming within 5.5% of an ideal PIM mechanism.